Answer:
Option D is correct.
Explanation:
The vertex is (-3,6)
We will check which equation satisfies the given vertex.
A) y = -3(x-3)^2 - 6
if x = -3 then value of y should be 6
Checking:
y = -3(-3-3)^2 - 6
y = -3(-6)^2 - 6
y = -3(36) -6
y = -114
if x= -3, y ≠ 6
B) y = -3(x+3)^2 - 6
if x = -3 then value of y should be 6
Checking:
y = -3(-3+3)^2 - 6
y = -3(0)-6
y = -6
if x= -3, y ≠ 6
C) y = -3(x-3)^2 + 6
if x = -3 then value of y should be 6
Checking:
y = -3(-3-3)^2 + 6
y = -3(-6)^2 + 6
y = -3(36) + 6
y = -102
if x= -3, y ≠ 6
D) y = -3(x+3)^2 + 6
if x = -3 then value of y should be 6
Checking:
y = -3(-3+3)^2 + 6
y = -3(0)^2 + 6
y = 6
So, if x= -3, y =6 so, if the vertex of parabola is at (-3,6) the equation will be
y = -3(x+3)^2 + 6
So. Option D is correct.